The unicellular origins of complex physiology - Torday, John S. (Henry Stewart Talks, 2016)
Cholesterol’s critical role in the evolution of eukaryotes, Vertical integration of calcium/lipid epistasis throughout vertebrate physiology, The unicellular perspective: aspects of physiology simplified, Simplification of physiology: homologies unseen by descriptive physiology, Physiology as fractal expressions of the unicellular state, The fractal principle: functional integration of physiology from first principles